Narasi Membangun Selebrasi: Gulir Ritual Kekristenan Awal - Rasid Rachman (Asosiasi Teolog Indonesia, 2020)
At its inception, Christian worship emerged from social conversations around a feast table. During Christianity’s earliest moments, these dining hall conversations shaped the (plural) narratives concerning the death of Christ. In this article, I trace the manner in which Christ’s death narratively fomented and fostered a messianic hope within the life of the earliest Christian communities. Central to my thesis is that the expression of such a hope then birthed the narrative of resurrection and of Jesus’ eventual return. The Evangelists, who developed these narratives in turn, did so by collecting stories from several sources, so that they might fashion a revised narrative—a retelling—of the life, work, death, and resurrection of Jesus the Messiah. I demonstrate that such narratives concerning Jesus thus materialize within the very form of ritual worship (liturgy) that had been characteristic of the fellowship enjoyed by the Primitive Church. These rites and practices entailed worship on the first day (Sunday worship), the Divine Office (daily prayers according to the hours), Paschal (Easter) worship, and baptism (ritualistic initiation). At the same time, even these worship rites themselves (re)narrate the story of Christ—with everything becoming intertwined, both bound up together and unfurling as a scroll. The worship rites of today’s church thereby comprise a heritage that stems from the celebratory feasts and mealtime stories of an anticipatory antiquity.